Characteristics of primary extranodal marginal zone B-cell lymphoma in Korea: conjunctiva versus other ocular adnexa. Issue 4 (16th August 2017) - Nam, Seung Wan; Woo, Kyung In; Kim, Yoon-Duck
Abstract : Aims: To compare the clinical characteristics and prognosis of primary conjunctival versus other ocular adnexal extranodal marginal zone B-cell lymphoma (EMZL). Methods: Retrospective review of clinical records for all consecutive patients with primary ocular adnexal EMZL treated from March 1995 to December 2015. Results: 198 patients were evaluated including 81 with primary conjunctival and 117 with other ocular adnexal EMZL. Conjunctival EMZL was found at a younger age (40.3±10.3vs 54.3±13.4 years, p<0.0001) with a female predilection (75.3%vs35.9%, p<0.0001) and had a higher rate of bilaterality (40.7%vs11.1%, p<0.0001) and a lower rate of systemic involvement (1.2%vs9.4%, p=0.030) compared with other ocular adnexal EMZLs. Conjunctival EMZL also showed a higher rate of complete response to primary treatment (98.8%vs89.5%, p=0.016) than other ocular adnexal EMZLs; however, recurrence and lymphoma-related death rates were not different between the two groups (p>0.05). Kaplan-Meier estimates for disease-specific survival at 5 and 10 years were 98.2% and 98.2% in conjunctival and 98.6%, respectively, and 95.2% in other ocular adnexal EMZLs. Univariate analysis showed that systemic involvement was negatively associated with conjunctival tumour location and positively associated with age (OR=0.35 and OR=1.05, p=0.045 and p=0.012, respectively), and treatment response was positively associated with conjunctival tumour location and negatively associated with age (OR=3.02 and OR=0.95, p=0.035 and p=0.009, respectively). Conclusions: Conjunctival EMZL shows unique demographic characteristic compared with other ocular adnexal EMZLs. Long-term follow-up is required due to late recurrence in ocular adnexal EMZL.